PROBLEMATIKA PENGATURAN DAN PENERAPAN SANKSI PIDANA ATAS PELANGGARAN PASAL 15 UNDANG-UNDANG NOMOR 24 TAHUN 2011 TENTANG BADAN PENYELENGGARA JAMINAN SOSIAL - Abdul Khakim (Universitas Muhammadiyah Malang, 2021)
The purpose of this paper analyzes the differences in sanctions regulation for violations of Article 15 and Article 19 of Law No. 24 of 2011 on Social Security Administering Body (Law 24/2011), which is a violation of Article 15 of Law 24/2011 subject to administrative sanctions (based on Article 5 PP 86/2013), while violations of Article 19 paragraph (1) and (2) of Law 24/2011 are subject to criminal sanctions (based on Article 55 of Law 24/2011). This study used normative juridical research methods. The results of this study show that there is a gap in the regulation and application of sanctions between Article 15 and Article 19 of Law 24/2011, whereas substantive violations of both articles are the same, because employers do not register themselves and their workers as participants to the Social Security Administering Body (BPJS). In fact, it aims to avoid the collection and payment of dues of participants who are responsible to BPJS. It should be a violation of Article 15 of Law 24/2011 not subject to administrative sanctions, but criminal sanctions article 55 of Law 24/2011 as well as Article 19 paragraph (1) and (2) Law 24/2011. The problem is constrained by the principle of legality in criminal law and depends on the ‘Courage’ of the judge to make a legal discovery. Conclusions obtained in the study are: (a) open possibility of application of criminal sanctions (ultimum remedium)against violations of Article 15 of Law 24/2011; (b) the occurrence of dissent against the possible application of criminal sanctions for violations of Article 15 of Law 24/2011 due to the separation of sanctions arrangements; (c) Employees of The Manpower Supervisory (PPK) must be observant and committed in law enforcement, especially against violations of Article 15 of Law 24/2011; and (d) on the issue of differences in sanctions it needs a deep understanding and built comprehensive legal construction as well as the need for legal discovery by judges.